Analysis of Repurchase Decision on the Tokopedia Marketplace with Consumer Satisfaction as a Moderating Variable - Rizqiani, Jevita; Efriyani Sumastuti; Ika Indria Sari (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The aim of this research is to ascertain and determine the relationship between the influence of service quality, brand image, customer experience, and website quality on repurchase choices with consumer satisfaction as a moderating variable. This research was conducted on 2020 PGRI Semarang University students as respondents in the Tokopedia marketplace. A total of 337 respondents were included in a purposive sampling strategy, which was used in conjunction with quantitative research methodology. Through the use of Google Forms, a questionnaire was distributed to collect primary data for this research. The data analysis method utilizes SmartPSL 3.0 Structural Equation Modeling (SEM) processing. Research findings show that repeat purchase decisions on the Tokopedia marketplace are positively and significantly influenced by brand image and customer experience. Meanwhile, service quality and website quality have an insignificant influence on repurchase decisions on the Tokopedia marketplace. Furthermore, the results of hypothesis testing show that the consumer satisfaction variable is successful in moderating the relationship between website quality and repeat purchase decisions. However, consumer satisfaction is not able to moderate the relationship between the variables of service quality, brand image, customer experience and repeat purchase decisions.